Gut Bacterial Communities of Dendroctonus valens and Monoterpenes and Carbohydrates of Pinus tabuliformis at Different Attack Densities to Host Pines - Xu, Dandan; Xu, Letian; Zhou, Fangyuan; Wang, Bo; Wang, Shanshan; Lu, Min; Sun, Jianghua (Frontiers in Microbiology, 2018)
Insects harbor a community of gut bacteria, ranging from pathogenic to obligate mutualistic organisms. Both biotic and abiotic factors can influence species composition and structure of the insect gut bacterial communities. Dendroctonus valens is a destructive forest pest in China. To overcome host pine defenses, beetles mass-attack the pine to a threshold density that can exhaust pine defenses. The intensity of pine chemical defenses and carbohydrate concentrations of pines can be influenced by beetle attack, both of which are known factors that modify beetle’s gut microbiota. However, little is known to what extent variation exists in the beetle's gut communities, and host monoterpenes and carbohydrates at different attack densities. In this study, the gut bacterial microbiota of D. valens at low and high attack densities were analyzed, and monoterpenes and carbohydrates in host pine phloem were assayed in parallel. The results showed that no significant changes of gut bacterial communities of the beetles and concentrations of D-glucose, D-pinitol and D-fructose in pine phloem were found between low and high attack densities. The concentrations of α-pinene, β-pinene, limonene at high attack densities were significantly higher than those at low attack densities. Our results suggested that different attack densities of D. valens influence monoterpenes concentration of host pines’ phloem but have no significant impact on gut bacterial community structures of D. valens and carbohydrate concentration of host trees’ phloem in early attack phase. Similar gut bacterial community structures of D. valens between low and high attack densities might be due to the quick adaptation of gut microbiota to high monoterpenes concentrations.